Design and Construction of a Chicken Egg Stamping and Weight Grading Machine Prototype at the Peruvian Company Agropecuaria Aviporc S.A.C. - León, Ryan (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4822 This article aims to design and build an egg stamping and weight grading machine prototype for the company Agropecuaria Aviporc S.A.C. Ten performance tests were carried out to grade chicken eggs according to the weight classification. It was concluded that the grading efficiency for grade A eggs was 100% and for grade B was 80%. Therefore, the prototype is a useful tool for egg grading and for cost and time reduction.